KAJIAN ANALISIS USAHA TERNAK KAMBING DI DESA LUBANGSAMPANG KECAMATAN PITURUH KABUPATEN PURWOREJO - Zulfanita . (MEDIAGRO, 2011)
The objective of this research is to find out about profits, incomes, and feasibility of goats  in Lubangsampang village, Pituruh sub-district in Purworejo regency. The research was conducted from March until April in 2008. The location and 26 respondents are the which were taken by the purposive sampling method. The analysis method consists of  income analysis and feasibility analysis.  This research shown that the income of respondents was around Rp. 2.888.000,  and feasibility analysis (R/C) was around 1.03. The research can be concluded that the goat farm  in Lubangsampang  village, Pituruh sub-district in Purworejo regency is feasible to conducting. Keywords: Goat, Income, Feasibility.